Seismic analysis of the Roman Temple of Évora, Portugal - Oliveira, Daniel V. (2012)
The Roman temple of Évora dates back to the 1st century AD and has undergone several changes throughout history, including various additions, which have been removed. Several archaeological studies have recently been carried out, but the structural safety of the temple is unknown. Of particular concern is the temple’s seismic resistance, as it is located in a region subjected to a moderate seismic hazard. The main purpose of this paper is to ascertain the temple’s behaviour under seismic excitation through limit analysis and discrete element analysis. Both analysis techniques will use the assumption that the structure is composed of rigid blocks connected with dry joints. Geometric information has been derived from a recent laser scanning surveying, while calibration undertaken using in-situ results from GPR and dynamic identification tests. The main results are presented and discussed in detail as well as the need for possible repair works within the framework of the ICARSAH guidelines.